Parental Involvement in Learning Programs for Children with Special Needs in Indonesia - Muhaimi Mughni Prayogo; Kristi Wardani; Haniek Farida (Universitas PGRI Adi Buana Surabaya, 2023)
The practice of education in schools still needs to improve in the form of limited studies focusing on parental involvement in the learning process of children with special needs in Indonesia. This study aimed to identify the forms of parental involvement in planning, implementing, and evaluating learning programs from 2017 to 2022 using the Systematic Literature Review (SLR) method. The stages of implementation using the Cooper version are (1) formulating the problem, (2) collecting data, (3) evaluating the feasibility of the data, (4) analysis and interpreting the relevant data, and (5) organizing and presenting the results. Data was collected by searching for keywords related to the concept to be reviewed on the data source page (Google Scholar, Perpusnas.go.id, and Portal Garuda). The results of this study indicate that parental involvement in learning planning is as a giver and recipient of information about the child's condition in the assessment process but has yet to be involved in determining the learning program. Meanwhile, mostly parents accompanied children when studying at home during the pandemic, despite many challenges in the learning implementation. As for the evaluation process, parents monitored their children’s progress and gave feedback to the teachers about their children’s achievements. The findings of this study indicate the need for further studies to improve school-parent collaboration in Indonesia.